Monetary policy in a world with different financial systems - Ester Faia (European Central Bank (ECB), 2002)
Major currency areas are characterized by important differences in financial structure that are clear in microeconomic data. Surprisingly, this fact is seldom discussed in the analysis of the international transmission of shocks. This paper attempts to fill the gap. First, I show some stylized facts about financial differences and cyclical correlations among the main OECD countries. Second, using a two-country model with monopolistic competition and sticky prices, calibrated to US and euro area data, I analyze the international transmission of shocks with different degrees of financial fragility in the two economies. I find, first, that financial diversity can account for heterogenous business cycle fluctuations. Differential responses to shocks are shown to occur with independent monetary policies - Taylor rules or rigid inflation targets - even with low degrees of economic and financial openness. Credible pegs help to increase the synchronization of cycles. Secondly, differences in persistence of the interest rates help to explain high persistence in the real exchange rate. Finally, weak financial systems can result in large welfare losses under symmetric and correlated shocks.
Keywords: E3; E42; E44; E52; F41; 330; differential transmission mechanism; Financial diversity; financial stability; monetary regimes; welfare losses